2009
DOI: 10.1080/09540120802385595
|View full text |Cite
|
Sign up to set email alerts
|

Reducing vertical HIV transmission in Kinshasa, Democratic Republic of Congo: trends in HIV prevalence and service delivery

Abstract: Scale-up of vertical HIV transmission prevention has been too slow in sub-Saharan Africa. We describe approaches, challenges, and results obtained in Kinshasa. Staff members of 21 clinics managed by public servants or non-governmental organizations were trained in improved basic antenatal care (ANC) including nevirapine (NVP)-based HIV transmission prevention. Program initiation was supported on-site logistically and technically. Aggregate implementation data were collected and used for program monitoring. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…Of the 41 included studies, 17 described PMTCT programs in low-income [46][50], [52][55], [57][59], [61][63], [67], [80], 15 in lower-middle income [41], [43][45], [56], [64], [65], [70], [72], [74], [76][79], [81], and nine in upper-middle income countries [42], [51], [60], [66], [68], [69], [71], [73], [75]. The presented PMTCT programs were implemented at different time periods between years 1997 and 2006 (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 41 included studies, 17 described PMTCT programs in low-income [46][50], [52][55], [57][59], [61][63], [67], [80], 15 in lower-middle income [41], [43][45], [56], [64], [65], [70], [72], [74], [76][79], [81], and nine in upper-middle income countries [42], [51], [60], [66], [68], [69], [71], [73], [75]. The presented PMTCT programs were implemented at different time periods between years 1997 and 2006 (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported that the confidentiality of counseling was not always achieved due to partially opened doors, interruptions during counseling and lack of space for counseling [50], [59], [60]. Several studies presented activities undertaken to ensure confidentiality of counseling, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 This package, instituted in June 2010 in 37 of the city’s highest volume facilities, has been described previously. 2426 …”
Section: Methodsmentioning
confidence: 99%